In vitro regeneration and callus induction of Oryza sativa L. Var. MRIA 1 / Nor Yasmin Mohamad Fauzi - Mohamad Fauzi, Nor Yasmin (2016)
A study was conducted to determine the effects of different plant regulators (PGR) towards in vitro regeneration and callus induction of new Malaysian rice variety of Oryza sativa L. var. MRIA 1. Intemode explants of 4-week old of aseptic seedlings were selected for in vitro regeneration and a total of 16 types of different combinations of NAA, IBA, BAP, and Kn were utilised. The most suitable plant growth regulators (PGR) for regeneration of Oryza sativa L. var. MRIA 1 was obtained from MS (Murashige and Skoog) media supplemented with 1.0 mg/L NAA and 0.5 mg/L Kn with an average of 8.90 ± 1.79 number of shoots per explant, 114.00 ± 18.90 number of roots per explant, 10.70 ± 2.62 cm length of shoots per explant and 8.70 ± 1.64 number of leaves per explant. The effect of combination of different plant growth regulators (PGR) supplemented in culture media on dry weight of regenerated Oryza sativa L. var. MRIA 1 were determined. Highest fresh weight (4.35±1.57 g) and dry weight (0.44±0.11 g per explant) recorded on the MS media supplemented with 1.0 mg/L NAA and 0.5 mg/L Kn. The callus inductions were assessed from three different explants including root, internode, and leaf base. The findings showed that the addition of 1.0 mg/L BAP into MS media was the most suitable for callus induction from root explant since it yield the highest fresh weight (1.039 ± 0.935 g per explant) and dry weight (0.093 ± 0.065 g per explant). The findings provided and optimum plant growth regulators (PGR) concentration for the tissue culture sysytem of Oryza sativa L. var. MRIA 1. Acclimatization of regenerated Oryza sativa L. var. MRIA 1 is recommended in order to serve a complete in vitro regeneration protocol of Oryza sativa L. var. MRIA 1.